When does credibility matter? The assessment of information sources in teenagers navigation regimes. (March 2023) - Almeida, Carla; Macedo-Rouet, Mônica; de Carvalho, Vanessa Brasil; Castilhos, Washington; Ramalho, Marina; Amorim, Luís; Massarani, Luisa
The aim of this paper is to investigate when and how Brazilian teenagers assess the credibility of information sources. We analyze data collected through focus groups, guided internet searches, and interviews with sixty-one 14- to 19-year olds from the state of Rio de Janeiro. Participants used different criteria to attribute credibility to information sources, with expertise and reputation being two of the most relevant, placing specialists, teachers, and the mainstream media at the top of their list of credible sources. Interestingly, these sources are not necessarily the ones that are most present in their daily lives, and credibility is only a relevant factor in some circumstances. Based on our results and data from other studies on the topic, we propose three navigation regimes (dilletante, motivated, and constrained) as a framework for analyzing teenagers' information evaluation behavior, in which the role of sources' credibility varies considerably. We believe this framework can help in the development of more effective strategies for improving young people's sourcing skills and media literacy.